Mengenali dan Mengelola Emotional Eating pada Remaja: Implementasi Penyuluhan dan Skrining di Sekolah Menengah Atas - Anindita, Yustika Izziyatu; Fithriyah, Izzatul; Hariyono, Agus (Civiliza Publishing, 2025)
Adolescents are an age group vulnerable to emotional pressure that can affect eating patterns, one of which is emotional eating—eating behavior in response to negative emotions. In semi-urban areas like Lamongan, this phenomenon has begun to emerge, but there has been limited education or screening related to it. The initiative aims to enhance adolescents' understanding of emotional eating, its causes and impacts, and to equip them with adaptive emotion regulation strategies through counseling and screening activities. Screening was conducted on 870 grade 10–11 students at SMAN 1 Lamongan using the EADESS questionnaire to assess the likelihood of emotional eating behavior. A total of 865 questionnaires were valid for analysis. The results showed that 100% of respondents experienced emotional eating at varying levels of severity: 83.35% mild, 13.53% moderate, 1.85% severe, and 1.27% very severe. Emotional eating was more prevalent among students who were overweight or obese. Emotional eating is a significant issue among high school adolescents. Counseling and screening have proven to be an important initial step in raising students’ awareness and understanding of the connection between emotions and eating behavior. Further education and accessible mental health services within schools are needed.